Creating a culture for radical innovation in a small mature business. (June 2018) - McLaughlin, Patrick
This article describes an approach in organizational development to develop an innovation culture for radical product development in a small mature engineering company. The research took place in a business based in the United Kingdom that designed and manufactured instrumentation and specialized packing machines. An initial study within the company's new product development team identified key aspects that influenced a radical innovation culture. Nine key themes were found to be pertinent, following an iterative process with the development team. These themes were triangulated using the established Organization Culture Assessment Instrument and the Creative Climate Assessment Tool. A third assessment was developed that gauged the development team culture proximity to an ideal position. Seven interventions were developed in conjunction with the company development team, senior managers, the analysis of previous empirical case research and dialogue with UK companies that promote discontinuous innovation. The results of the interventions were evaluated 4 years after implementation. The culture was re-assessed using the same assessment tools and the changes were identified. The outcomes are described and they indicate the success of the company's attempt to embed a sustainable radical innovation culture into the product development area.